Ugi reaction synthesis of oxindole-lactam hybrids as selective butyrylcholinesterase inhibitors - Burke, Anthony (2022)
Molecular hybridization is a valuable approach in drug discovery. Combining it with multicomponent reactions is highly desirable, since structurally diverse libraries can be attained efficiently in an eco-friendly manner. In this work, isatin is used as the key building block for the Ugi 4-center 3-component reaction synthesis of oxindole–lactam hybrids, under catalyst-free conditions. The resulting oxindole−β-lactam and oxindole−γ-lactam hybrids were evaluated for their potential to inhibit relevant central nervous system targets, namely cholinesterases and monoamine oxidases. Druglikeness evaluation was also performed, and compounds 4eca and 5dab exhibited great potential as selective butyrylcholinesterase inhibitors, at the low micromolar range, with an interesting predictive pharmacokinetic profile. Our findings herein reported suggest oxindole–lactam hybrids as new potential agents for the treatment of Alzheimer’s disease.